2002
DOI: 10.1021/bi012000x
|View full text |Cite
|
Sign up to set email alerts
|

Design, Pharmacology, and NMR Structure of a Minimized Cystine Knot with Agouti-Related Protein Activity

Abstract: The agouti-related protein (AGRP) is an endogenous antagonist of the melanocortin receptors MC3R and MC4R found in the hypothalamus and exhibits potent orexigenic activity. The cysteine-rich C-terminal domain of this protein, corresponding to AGRP(87-132), exhibits receptor binding affinity and antagonism equivalent to that of the full-length protein. The NMR structure of this active domain was recently determined and suggested that melanocortin receptor contacts were made primarily by two loops presented by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 43 publications
2
105
0
2
Order By: Relevance
“…The computations included three steps: (1) comparative model of ASIP(93-132), which demonstrates 50% homology to AGRP(87-132), using a higher quality NMR structure of AGRP(87-120) [1mr0 (8)] as a template for the first 34 residues and a second NMR model of a longer fragment AGRP(87-132) [1hyk (18)] as a template for the C-terminal loop 121-132, (2) homology modeling of MCR1 and MCR4, based on the crystal structure of rhodopsin (1gzm) (26), and (3) calculation of three receptor-antagonist complexes using our mutagenesis data to identify residues important for binding of ASIP(93-132) and AGRP(87-132) by the corresponding receptors.…”
Section: Methodsmentioning
confidence: 99%
“…The computations included three steps: (1) comparative model of ASIP(93-132), which demonstrates 50% homology to AGRP(87-132), using a higher quality NMR structure of AGRP(87-120) [1mr0 (8)] as a template for the first 34 residues and a second NMR model of a longer fragment AGRP(87-132) [1hyk (18)] as a template for the C-terminal loop 121-132, (2) homology modeling of MCR1 and MCR4, based on the crystal structure of rhodopsin (1gzm) (26), and (3) calculation of three receptor-antagonist complexes using our mutagenesis data to identify residues important for binding of ASIP(93-132) and AGRP(87-132) by the corresponding receptors.…”
Section: Methodsmentioning
confidence: 99%
“…12 Oxidative folding was performed in a mixture of oxidized and reduced glutathione and low concentrations of guanidinium. 13 A wide series of conditions were explored, however, the best yield relative to pure unfolded peptide was approximately 10%. An analytical HPLC trace of ASIP(80-132) following a folding trial is shown in Figure 1(a).…”
Section: Design Synthesis and Pharmacology Of A Functional Asip C-tementioning
confidence: 99%
“…This proposal is also consistent with our previous observation that AgRP(87-120), a mini-protein that contains only the central and N-terminal loops, exhibits MCR selectivity and antagonism equivalent to that of the full AgRP C-terminal domain. 13 Alternative conformations of ASIP-YY, dictated by the cis-trans isomerization of the Ala104-Pro105 peptide bond, contain a persistent cis peptide bond at Pro102-Pro103, yet the N-terminal loop of AgRP is devoid of cis Xaa-Pro bonds. As demonstrated by our mutagenesis studies, this apparent paradox is explained because a single cis bond at either position of ASIP-YY yields a protein with significantly reduced activity, while two cis bonds yield a protein with normal activity.…”
Section: The Structures Of Asipmentioning
confidence: 99%
“…Along with the NMR structure of AGRP (the endogenous antagonist of melanotropin) (PDB: 1HYK) [66] and MTII (potent agonist) [67], the 3D pharmacophore of human melanocortin receptor ligands has been partially deciphered. Results from these biophysical and chemical studies can be crucial for designing novel selective agonist and antagonist melanotropins [52].…”
Section: Using Nmr Based Modeling and Computational Methods For Melanmentioning
confidence: 99%